ANALYSIS OF TELECOMMUNICATION TOWER ACCOUNTING AT PT. SARANA MENARA NUSANTARA TBK. PERIOD 2014-2015 - Anggraeny, Shinta Noor; Oktavia, Trisna Ayu; Sugiharto, Sugiharto (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2020)
This study aims to determine the accounting treatment of telecommunication tower companies, especially PT. Sarana Menara Nusantara Tbk. which recognized telecommunications towers as fixed assets in 2014 and recognized as investment properties in 2015 and the impact of their accounting for that period.This type of research is qualitative research, using interpretive descriptive methods. Data presented in descriptive form without processing with other analytical techniques. With this research, information is expected to equalize perceptions related to differences that occur regarding differences in recognition of telecommunications towers and to assist companies in evaluating performance, especially in terms of achieving earnings.